Incidence Trends of Rheumatoid Arthritis in Korea for 11 Years (2006–2017) - Hanna Lee; Sang-Il Lee; Hyunjin Lim; Hyun-Ok Kim; Rock Bum Kim; Yun-Hong Cheon (Clinics and Practice)
Background/Objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disorder characterized by joint damage. However, no incidence analyses have been conducted on a Korean population since 2013. We aimed to calculate the incidence of RA and examine trends using complete Korean National Health Insurance Service claims data from 2007. Methods: We used 16 years of Korean NHIS claims data from 1 January 2002 to 31 December 2017. Patients were defined as having RA when diagnosed with ICD-10 codes M05 and M06. We set the 5-year period prior to 2006 as disease-free. Results: From 2007 to 2017, the incidence rate of RA was 35 to 43 per 100,000 individuals. The female-to-male ratio was approximately 3–3.5 to 1. The sex-standardized incidence rate was highest in the 60–69 age group but gradually declined, resulting in a reversal in 2017, with the highest incidence rate observed in the 50–59 age group. The incidence of elderly onset RA (EORA) in individuals aged >60 years exhibited a decreasing trend during the study period (age 60–69, −6.45, 95% CI = −8.27 to −4.62, p < 0.001; age ≥70, −6.09, 95% CI = −7.66 to −4.53, p < 0.001). Conclusions: This study is the first to analyze the incidence trend of RA over an 11-year period. In South Korea, the incidence of RA has shown a decreasing trend since 2011; the same trend was observed in the EORA group. Young-onset RA showed the opposite trend, suggesting that RA is diagnosed earlier, due to the new RA classification criteria.